Petrophysical characterizations of Mishrif Formation in Selected Wells of Tuba Oil Field, Southern Iraq - Mohammed, Mustafa Jawad; Mahdi, Thamer A. (Iraqi Journal of Science, 2019)
The current study includes building (CPI) & Petrophysical Evaluation of the Mishrif Formation (Cenomanian-Early Turonian) in Tuba oilfield, southern Iraq by using Interactive Petrophysics Program v3.5 (IP) to evaluate different logs parameters that control the reservoir quality of Mishrif Formation such as shale volume, effective porosity, and water saturation. Mishrif Formation is subdivided into several units, which are characterized by different reservoir properties. These units are Top of Mishrif, MA, CR2, MB1, and MB2.The results of computer processed interpretation (CPI) show that the major reservoir unit are (MB1 and MB2), which are characterized by high effective porosity and oil saturation. In addition, these units consist of vuggy rudist-bearing facies. The units TM,MA have lower reservoir quality due to low values of effective porosity and high water saturation .The low effective porosity in these units is related to the dominance of lime-mud rich facies that are recognized in deep marine and lagoon facies associations. The unit CR2 represents a cap unit, which extends in all studied wells.